Papers - Production - Domestic - Oil and Gas Development in Ohio for 1937 - Dewitt T. Ring (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1938)
Reliable and detailed data covering the enormous number of wells drilled and the long historical production of the state, many of which were never recorded until recent years, render it impossible to gather statistical material suitable for the Institute's standardized form. The total production of crude oil in Ohio for the year was 3,654,503 bbl., which is less than the total production in the United States for the peak day of August 1937. For a period of eight years, from 1895 to 1902 inclusive, Ohio produced more oil than any other state. During the year, 1271 tests were drilled in the state, or 114 more than in 1936. Of these, 317 were oil wells, with an initial production of 7088 bbl., an average of 22.3 bbl. per well; 503 were gas wells, with an initial open flow of approximately 222,441 M cu. ft., or 443 M cu. ft. per gas well drilled; 451 were dry holes, that is, 35 per cent of the total completions. A number of factors account for the steady decline of oil production in Ohio. In the state, at the close of thc year, there were fewer than 28,122 producing oil wells. In 1936, there were 30,150 operated oil wells with an average yearly production per well of 126 bbl. The production for 1937 averaged 130 bbl. per well. During the year, 2028 oil wells were abandoned. In other words, old wells are being abandoned more than six times faster than new ones are being drilled. Since the inception of the oil and gas industry in Ohio, between 150,000 and 160,000 wells have been drilled in the state; new potential territory, offering desirable locations for either oil or gas, is becoming increasingly more difficult to find; the dry-hole percentage will continue to increase. Prices Another factor directly affecting the crude situation during the year was the matter of price and proration of Pennsylvania grade oil. The posted price for Pennsylvania grade in Ohio on June 7 was $2.37 per barrel; at the close of the year, it was $1.70 per barrel, or a reduction of 28 per cent in price. In addition to this price cut, a 50 per cent pro-